2004
DOI: 10.1523/jneurosci.0450-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Dorsal Cochlear Nucleus Neurons to Signals in the Presence of Modulated Maskers

Abstract: The detection of a signal in noise is enhanced when the masking noise is coherently modulated over a wide range of frequencies. This phenomenon, known as comodulation masking release (CMR), has been attributed to across-channel processing; however, the relative contribution of different stages in the auditory system to such across-channel processing is unknown. It has been hypothesized that wideband or lateral inhibition may underlie a physiological correlate of CMR. To further test this hypothesis, we have me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 40 publications
5
56
0
Order By: Relevance
“…Together, we suggest that although the detection of the tone could occur in IC, or even lower (Pressnitzer et al, 2001;Neuert et al, 2004), the tone representation is more explicit in MGB and even more so in A1.…”
Section: Locking Suppression By Low-level Tonesmentioning
confidence: 75%
See 1 more Smart Citation
“…Together, we suggest that although the detection of the tone could occur in IC, or even lower (Pressnitzer et al, 2001;Neuert et al, 2004), the tone representation is more explicit in MGB and even more so in A1.…”
Section: Locking Suppression By Low-level Tonesmentioning
confidence: 75%
“…A major challenge in auditory neuroscience is to understand how the auditory system segregates low-level signals embedded in masking noise (Phillips and Cynader, 1985;Ramachandran et al, 2000;Neuert et al, 2004). Humans and animals perceive lowlevel signals embedded in slowly fluctuating noise more efficiently than similar signals embedded in unmodulated noise (Schooneveldt and Moore, 1989;Klump and Langemann, 1995;Langemann and Klump, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Medial OC neurons are known to have collaterals projecting to the CN (Winter et al, 1989;Benson and Brown, 1990;Benson and Potashner, 1990;Brown, 1993;Benson et al, 1996;Horváth et al, 2000), and we have previously shown direct excitatory effects of these collaterals on CN neurons, in particular onset chopper neurons (Mulders et al, 2002(Mulders et al, , 2003(Mulders et al, , 2007). These neurons are thought to provide wide band inhibition to other CN neurons (Verhey et al, 2003;Arnott et al, 2004;Neuert et al, 2004) and could be responsible for the modulation of spontaneous activity remaining after cochlear strychnine. Further investigations are required to determine the exact cause of the extensive effects on spontaneous rate when the peripheral effects of the OC system are blocked.…”
Section: Discussionmentioning
confidence: 99%
“…Rhode and Greenberg 1994;Joris et al 1994;Moller 1976) and the inferior colliculus (e.g., Nelson and Carney 2007;Krishna and Semple 2000;Langner and Schreiner 1988;Muller-Preuss et al 1994;Rees and Moller 1983). However, very few studies have directly tested the neuronal correlates of signal detection when the masker is temporally modulated (CN: Pressnitzer et al 2001;Neuert et al 2004). The studies in the cochlear nucleus found that very few neurons in the ventral CN showed neuronal correlates of enhanced thresholds such as those seen in behavior (Pressnitzer et al 2001).…”
Section: Bohlen Et Al: Detection Of Modulated Tones In Modulated Noisementioning
confidence: 99%
“…The studies in the cochlear nucleus found that very few neurons in the ventral CN showed neuronal correlates of enhanced thresholds such as those seen in behavior (Pressnitzer et al 2001). However, a majority of neurons in the dorsal CN showed such neuronal correlates (Neuert et al 2004), and these threshold enhancements were postulated to result due to wideband inhibition. However, magnitude of neuronal threshold changes in the dorsal CN could not account for behavioral threshold changes.…”
Section: Bohlen Et Al: Detection Of Modulated Tones In Modulated Noisementioning
confidence: 99%